2022
DOI: 10.1097/aci.0000000000000881
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and childhood asthma

Abstract: Purpose of reviewAsthma is the most common chronic disease of childhood. Environmental exposures, such as allergens and pollutants, are ubiquitous factors associated with asthma development and asthma morbidity. In this review, we highlight the most recent studies relevant to childhood asthma risk, onset, and exacerbation related to air pollution exposure.Recent findingsIn this article, we review current research that has been published between 2021 and 2022, demonstrating the effects of early-life exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Second, Ko and Hsu suggest that outdoor air quality or time spent outdoors could be reasons for the improvements in asthma in our study . Outdoor air quality can be an important determinant of child respiratory health, and increases in neighborhood safety and other factors associated with moving can affect the amount of time that children spend outdoors. We are currently working to incorporate outdoor air and school exposures in our continuation of this work.…”
mentioning
confidence: 68%
“…Second, Ko and Hsu suggest that outdoor air quality or time spent outdoors could be reasons for the improvements in asthma in our study . Outdoor air quality can be an important determinant of child respiratory health, and increases in neighborhood safety and other factors associated with moving can affect the amount of time that children spend outdoors. We are currently working to incorporate outdoor air and school exposures in our continuation of this work.…”
mentioning
confidence: 68%
“…Third, even though people have been aware of the harm that air pollution causes to the respiratory system and have made numerous efforts to reduce it, air pollution can still cause asthma in some areas. The idea that outdoor air pollution causes pre-existing asthma to worsen has been supported by decades of accumulating evidence, with some studies suggesting that outdoor air pollution can also cause new cases of asthma ( 32 ). Extreme weather events are becoming more common as a result of global climate change, which may also be a factor.…”
Section: Discussionmentioning
confidence: 99%
“…Urban areas had two-thirds of pediatric asthma incidence related to NO 2 exposure. A review of scientific publications between 2021 and 2022 demonstrated the harmful effects on respiratory health, especially pediatric asthma, of early exposure to pollutants such as nitrogen dioxide, sulfur dioxide and ozone, as well as tobacco smoke, radon and the presence of volatile organic compounds (VOCs) [15].…”
Section: Introductionmentioning
confidence: 99%